PDRB, POTENSI WILAYAH ANALISIS SEKTOR POTENSI DAN PENDORONG EKONOMI KABUPATEN BLITAR PROVINSI JAWA TIMUR TAHUN 2014-2019 - Dwi Reza Khusnul Khuluk (Oikos : Jurnal Ekonomi dan Pendidikan Ekonomi, 2021)
Economic development is an effort made by local governments to improve the welfare of the community, to improve regional economic development is necessary to develop economic sectors in policies used by local governments. The research aims to analyze how the potential of economic sector and sector that is the driver of economic growth in Blitar Regency, East Java Province, in this study used Location Quotient (LQ) analysis method and Shift Share (SS) analysis. The data used is secondary data obtained from central statistics agency East Java and using vulnerable people from 2014 to 2019, from this research obtained results that economic growth in Blitar regency is quite fast and in its development has experienced many ups and downs in the base and non-base sectors. The most potential sector is the accommodation and food supply sector.